1, 3‐Benzothiazoles as Antimicrobial Agents. (24th October 2014) - Defrenza, Ivana; Catalano, Alessia; Carocci, Alessia; Carrieri, Antonio; Muraglia, Marilena; Rosato, Antonio; Corbo, Filomena; Franchini, Carlo
Abstract : Starting from 2‐amino‐1, 3‐mercaptobenzothiazoles recently reported (1a, 1b, 1c, 1d, 1e, 1f, 1g, 1h ), a series of the corresponding 2‐mercapto‐1, 3‐benzothiazole isosters (2a, 2b, 2c, 2d, 2e, 2f, 2g, 2h ) were screened for their in vitro antibacterial and antifungal activities. Results underline that the presence of the mercapto moiety at the 2‐position of the heterocyclic nucleus is crucial for activity against bacteria. The biological screening against Candida spp. identified commercial2f as the most promising compound as antifungal against Candida albicans and tropicalis .Molecular modeling studies supported these results. Then, to enlargestructure‐activity relationship (SAR) studies on series1, newly synthesized compounds (1k, 1l, 1m, 1n, 1o, 1p ) were reported. All the compounds belonging to this series and bearing a bulky substituent at the 6‐position of the aryl moiety showed high antifungal activity. Abstract :